Peranan Citra Merek Produk Kartu Axis Terhadap Minat Beli Mahasiswa Politeknik Negeri Kupang - Hamzah Nazarudin; Herybertus M. L. Geto (STIE Widya Manggala, 2021)
The purpose of this study was to determine the role of the AXIS card product brand image on the buying interest of students at the Kupang State Polytechnic.The population and sample in this study were students of Kupang State Polytechnic who were interested in using the AXIS Card productand have characteristics according to research needs that can be used as respondents, The sampling technique used was nonprobability sampling.The data were collecte thorugh questionnaire. Technique for analyzing data was simple linear regression analysis. The writer collected data by spreading questionnaires to 45 students of Kupang State Polytechnic. Based onthe simple linear regression analysis, it is known that the equation was Y=4.378 + 0.589X therefore there is a positive influence between brand image and purchase intention. r square was 0.513 or it has influence of 51.3% on consumers’ purchase intention. Then, the result of hypothesis test showed that t count ≥ t table, it means that brand image influenced positively and significantly on purchase intention, with thesignificant value was 0.00 smaller than 0.05 so the relationship between brand image and consumers’ purchase intention was significant.